1998
DOI: 10.1093/ije/27.4.647
|View full text |Cite
|
Sign up to set email alerts
|

Maternal cotinine level during pregnancy and birthweight for gestational age

Abstract: Cotinine is a better predictor of birthweight than the reported number of cigarettes smoked. If biochemical analysis is impossible, then self-reported smoking habit should be obtained prospectively using a structured approach. Any effect on birthweight of maternal passive smoking during pregnancy is small compared with the effects of maternal active smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
73
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(79 citation statements)
references
References 26 publications
5
73
1
Order By: Relevance
“…Some studies 11,15,19,26,32,33) had examined the effect of ETSexposure measured by biochemical markers on fetal growth, but the findings were still conflicting. Biochemical markers could be regarded as objective and quantitative ETS-indicators, but could only provide ETS-exposure measured within a limited time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies 11,15,19,26,32,33) had examined the effect of ETSexposure measured by biochemical markers on fetal growth, but the findings were still conflicting. Biochemical markers could be regarded as objective and quantitative ETS-indicators, but could only provide ETS-exposure measured within a limited time.…”
Section: Discussionmentioning
confidence: 99%
“…Chen and Petitti 16) showed that the relative risk (RR) for term small-forgestational-age infants in association with passive smoke exposure was 0.47. In contrast, many other studies 4,6,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] have shown that ETSexposure during pregnancy harmfully affected fetal growth. These studies, however, ranged from studies claiming rather large effects to those showing small effects.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Some of these studies have used questionnaire data to determine ETS exposure ( Martin and Bracken, 1986;Chen et al, 1989;Mathai et al, 1992;Fortier et al, 1994;Roquer et al, 1994;Dejin -Karlsson et al, 1998), with five studies relying solely on information concerning household members who smoke, one as recently as 1997 (Brooke et al, 1989;Chen et al, 1989;Mathai et al, 1992;Saito, 1991;Ahluwalia et al, 1997 ). Other studies examining the association between ETS exposure and low birth weight have measured exposure using a biomarker such as cotinine (Eskenazi et al, 1995;Haddow et al, 1988;Peacock et al, 1988 ). Studies that determine exposure using a biomarker are more difficult to conduct and more expensive than questionnaire data.…”
Section: Introductionmentioning
confidence: 99%
“…Those most at risk from ETS exposure appear to be neonates, young children, and possibly the fetus (8). Study after study is finding that ETS exposure adversely affects fetal growth with an elevated risk of low birth weight (LBW) (9)(10)(11)(12)(13). The impact of passive smoking on other reproductive outcomes is less clear; an elevated risk of spontaneous abortion (14) and sudden infant death syndrome (15) as well as impaired female and male fertility (16,17) have been observed in some epidemiologic studies.…”
mentioning
confidence: 99%